Spatial information systems for sustaining the profitability of retailer business during the global meltdown economy - Bohari, Abdul Manaf; Rainis, Ruslan; Marimuthu, Malliga (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
Profitability is the central issues of world wide business firms, especially during the un-predictable situation under the global meltdown economy. Retailer is the most influenced by the crisis because it highly depends on the customers buying activity. In perspective of customers, the value that rewarded from purchasing activity is the most important consideration to continually transaction with the retailer. However, in perspective of retailers, they want to maximize the profit by utilizing their marketing efforts on selling the product to customers. As long as customer continues do the transaction, retailer believed that they can achieve their target. Critically, the contrast view of customer-retailer on the value will raise the issues on profitability and has identified as unsolved issues in the marketplace. Thus, this paper is highlighting the capability of Spatial Information Systems for sustaining the profitability of retailers. By utilizing this technology, it’s helps retailers in sustaining the retailer’s performance, via managing the customer value continuously and practically. Moreover, Spatial Information Systems provide tools and platform to analyzing the customer value in the marketplace, as the real geographical marketplace. Practical aspect of Spatial Information Systems applications are discussed with specific focus on retailer’s business. Moreover, the used of spatial information systems is practically important to the manager to make them understand on what are the real chances on customer value in the geographical marketplace. At the end, suggestion was made on how to choose the suitable Spatial Information Systems to retailers with considerations on the current financial matters.